The application of cogeneration systems to the cooling of food and buildings in East Timor : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology at Massey University - Saldanha, Estanislau de Sousa (Massey University, 2001)
Cogeneration is generation of both heat and power simultaneously using a single primary energy input. Cogeneration recovers "waste heat "from a conventional power generation plant to produce useful energy, leading to the increased overall efficiency of fuel input. This also achieves cost savings, and reduces greenhouse gas emissions where fossil fuels are used. The objectives of this study are to assess the technical and economic viability of a cogeneration system for the cooling of food and buildings in East Timor. The findings of this research provide a basis for recommending action and further research to East Timor's decision-makers on energy issues. Technical assessments in this study focus on cooling, electricity demand, and fuel supply as the basis for choosing the type and size of a cogeneration system. The financial viability of the cogeneration system is assessed using net present value (NPV) and sensitivity analysis. The NPV of the cogeneration system is compared with the NPV of conventional energy supply for cooling and electricity. There is low demand for cooling for comfort and food preservation in East Timor, due to low levels of industrial and commercial investment, and the vast majority of people still living in poverty. Although cooling demand is low overall, numerous government and commercial buildings have installed cooling systems. In this study, six buildings (2 office buildings, a bank, a hotel, a university and a mini-market) were selected based on their relatively high cooling demand and their geographic proximity to one another. The cooling demand of these six buildings was modeled based on a room-by- room approach. The results showed that their overall hourly cooling demand averages 600 kilowatt-cooling, while peak load was 707 kilowatt-cooling. This cooling demand was primarily driven by ambient temperature, number of people present and lighting load. Power demand in East Timor is low. The total operable power supply capacity for the entire country is 22 megawatts, of which more than half is located in Dili. Electricity demand is predominantly driven by residential consumption, rather than commercial and industrial consumption. Although there is low electricity demand, East Timor faces an immediate electricity deficit of 24 megawatts, which is higher than the existing operable capacity. In the six selected buildings, the overall peak and average electricity loads were 489 kW and 422 kW respectively. This load was mainly driven by air conditioning, computers, and lighting applications during working hours. Electricity generation relies on diesel, which is imported from Indonesia. Diesel will remain the main source to generate electricity due to a lack of feasible alternatives. East Timor is rich in natural gas both offshore and onshore. However, until now there has been no plan to provide natural gas distribution pipelines to East Timor. Based on the cooling and electricity demand and fuel availability, diesel was chosen to drive the cogeneration systems. The size of the cogeneration system was selected so as to fulfill both the electricity demand in the six selected buildings and be able to export surplus to the local grid. There are two reasons for employing a larger engine capacity. Firstly, a small engine will not be able to generate sufficient heat to drive an absorption cooling system with a capacity of 600 kilowatt. Secondly, export electricity will increase revenues generated from the cogeneration plant. Financially, the net present value (NPV) of both the cogeneration system and the conventional energy supply system were lower than zero, which means that neither system can be viable financially. The cogeneration system's NPV was lower than that for the conventional energy supply system, due to its higher capital and operating costs. High operating costs were due to fuel costs, with low revenues being due to heavy subsidies on electricity. If fuel and electricity subsidies were removed, a cogeneration system could become a more attractive option compared to a conventional system. However, removing the electricity subsidy would result in the large majority of people being unable to afford electricity.
Keywords: Cogeneration of electric power and heat; East Timor; Economic aspects; Refrigeration and refrigerating machinery